MENINGKATKAN HASIL BELAJAR FIQIH MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PICTURE AND PICTURE PADA SISWA KELAS VI - Soepratman, Soepratman (EDUCATOR : Jurnal Inovasi Tenaga Pendidik dan Kependidikan, 2025)
This Classroom Action Research (CAR) aims to improve the activity and learning outcomes of Fiqh of grade VI students of MIS Tuhfatul Athfal Sungai Raya through the application of the picture and picture type cooperative learning model. The study was conducted in two cycles, involving 24 students. Learning activity data were collected through observation, while learning outcome data were obtained through tests. The results of the study showed a significant increase in both aspects. Students' learning activities increased from the category of "sufficient" (average score of 2.6) in cycle I to "high" (average score of 3.8) in cycle II. The average value of learning outcomes also increased from 66 (cycle I) to 78 (cycle II). Classical completeness increased drastically from 50% in cycle I to 92% in cycle II. Based on these results, it can be concluded that the picture and picture type cooperative learning model is effective in improving students' Fiqh activity and learning outcomes. This model is recommended as a learning strategy to improve the quality of Fiqh learning. ABSTRAKPenelitian Tindakan Kelas (PTK) ini bertujuan untuk meningkatkan aktivitas dan hasil belajar Fiqih siswa kelas VI MIS Tuhfatul Athfal Sungai Raya melalui penerapan model pembelajaran kooperatif tipe picture and picture. Penelitian dilaksanakan dalam dua siklus, melibatkan 24 siswa. Data aktivitas belajar dikumpulkan melalui observasi, sedangkan data hasil belajar diperoleh melalui tes. Hasil penelitian menunjukkan peningkatan signifikan pada kedua aspek. Aktivitas belajar siswa meningkat dari kategori "cukup" (skor rata-rata 2,6) pada siklus I menjadi "tinggi" (skor rata-rata 3,8) pada siklus II. Nilai rata-rata hasil belajar juga meningkat dari 66 (siklus I) menjadi 78 (siklus II). Ketuntasan klasikal meningkat drastis dari 50% pada siklus I menjadi 92% pada siklus II. Berdasarkan hasil tersebut, dapat disimpulkan bahwa model pembelajaran kooperatif tipe picture and picture efektif meningkatkan aktivitas dan hasil belajar Fiqih siswa. Model ini direkomendasikan sebagai strategi pembelajaran untuk meningkatkan kualitas pembelajaran Fiqih.